1975
DOI: 10.1007/bf02532434
|View full text |Cite
|
Sign up to set email alerts
|

Response of lipogenesis and fatty acid synthetase to physical training and exhaustive exercise in rats

Abstract: The effect of physical training and exhaustive exercise on fatty acid synthesis in rat liver and adipose tissue has been investigated. Exercise training (treadmill running) significantly (p less than 0.05) decreased body wt, eipdidymal fat pad wt, adipocyte size, and hepatic fatty acid synthetase activity. Training did not significantly affect adipose tissue cell number, lipogenesis from glucose-U-14C, or fatty acid synthetase. Exercise to exhaustion immediately prior to sacrifice significantly (p less than 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 30 publications
1
2
1
Order By: Relevance
“…The increase in MAV and CS activity and the decrease in BM are consistent with previous findings on the effect of endurance training in rats (Askew et al. 1975, Hoppeler et al.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in MAV and CS activity and the decrease in BM are consistent with previous findings on the effect of endurance training in rats (Askew et al. 1975, Hoppeler et al.…”
Section: Discussionsupporting
confidence: 92%
“…These results are at variance with those of animal studies which have reported training effects only for insulin stimulated values (19,36). This could be due to the fact that each animal strain exhibits little genetic variation, but has a characteristic lipogenic activity (3,17). However, such is not the case with humans; each individual has a unique genetic profile such that the response to endurance training can be at variance with that observed in inbred rats.…”
Section: Discussioncontrasting
confidence: 61%
“…Askew et al [12] found decreased FAS activity in rat liver after exercise training and no difference in the adipose tissue. On the contrary, Faulconnier et al [13] found decreased activity of the enzyme in rat adipose tissue and no difference in the liver with exercise training.…”
Section: Introductionmentioning
confidence: 97%